Answer:
e= 2x-4
Step-by-step explanation:
the opposite of e is 2x-4.
We know that
if <span>(ax + b)(cx - d) = 0
then
</span><span>(ax + b)= 0-----> ax=-b------> x=-b/a
and
</span><span>(cx - d) = 0-----> cx=d------> x=d/c
therefore
the answer is the option
</span><span>C. -\frac{b}{a}</span>
- Multiply (-2x-4) by -5:
[(-5)(-2x) + (-5)(-4)] +5x - 4 = -29
= 10x+20+5x-4=-29
- Combine Like Terms:
(10x+5x) + (20-4) = -29
15x+16=-29
- Subtract 16 from each side
15x+16 -16 = -29 -16
15x = -45
x = -3
Answer:
jaxoscxhdnsidsbc
Step-by-step explanation:
aciowshavpaslkn oica xhkvsaih oilcs